Rendezvous between ambulances and prehospital physicians in the Capital Region of Denmark: a descriptive study - Roselil Oelrich; Julie Samsoee Kjoelbye; Oscar Rosenkrantz; Charlotte Barfod (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2022)
Abstract Background In a two-tier Emergency Medical Services response system with ambulances and physician-staffed rapid response vehicles, both units are ideally dispatched simultaneously when a physician is needed. However, when advanced resources are dispatched secondarily, a meeting point (rendezvous) is established to reduce time to advanced care. This study aims to assess the extent of rendezvous tasks, patient groups involved and physician contribution when rendezvous is activated between the primary ambulances and rapid response vehicles in the Capital Region of Denmark. Methods We analysed prehospital electronic patient record data from all rendezvous cases in the Capital Region of Denmark in 2018. Variables included the number of times rendezvous was activated, patient demographics, dispatch criteria, on-scene diagnosis, and prehospital treatment. Result Ambulances requested rendezvous 2340 times, corresponding to 1.3% of all ambulance tasks and 10.7% of all rapid response vehicle dispatches. The most frequently used dispatch criterion was unclear problem n = 561 (28.8%), followed by cardiovascular n = 439 (22.5%) and neurological n = 392 (20.1%). The physician contributed with technical skills like medication n = 760 (39.0%) and advanced airway management n = 161 (8.3%), as well as non-technical skills like team leading during advanced life support n = 152 (7.8%) and decision to end futile treatment and death certificate issuance n = 73 (3.7%). Conclusion Rendezvous between ambulances and physician-staffed rapid response vehicles was activated in 1.3% of all ambulance cases corresponding to 10.7% of all RRV dispatches in 2018. The three largest patient groups in rendezvous presented cardiovascular, neurological, and respiratory problems. The prehospital physician contributed with technical skills like medication and advanced airway management as well as non-technical skills like team leading during advanced life support and ending futile treatment. The high percentage of dispatch criterion unclear problem illustrates the challenge of precise dispatch and optimal use of prehospital resources. Therefore, it seems necessary to have a safe and rapid rendezvous procedure to cope with this uncertainty.